Long‐term adherence to apomorphine infusion in patients with Parkinson disease: a 10‐year observational study. Issue 5 (May 2017) - Kimber, Thomas E.; Fang, Jing; Huddy, Lynda J.; Thompson, Philip D.
Abstract : Background: Patients with Parkinson disease (PD) commonly experience motor fluctuations and dyskinesias in response to oral dopaminergic medications. Affected patients may benefit from device‐assisted therapy, such as medication infusion or deep brain stimulation surgery. This is the first Australian study of the long‐term adherence to apomorphine infusion (AI) in patients with PD. Aims: To assess the adherence to AI in patients with PD in a single centre over a 10‐year period and to find the reasons for discontinuation in patients who discontinued AI. Methods: This is an observational study of patients with PD treated with AI between 2004 and 2014. Outcome measures included changes in motor function and quality of life following AI, change in dose of other dopaminergic medications following AI, duration of infusion, adverse effects, reasons for cessation of AI and subsequent treatment after cessation. Results: Mean duration of AI was 21.65 months. No patient achieved apomorphine monotherapy, and the mean reduction in the levodopa‐equivalent dose of other dopaminergic medications after AI was 22.7%. The benefit of AI on motor function and quality of life was rated as 'much improved' or 'better' in 83% of patients. The most common reasons for discontinuation of AI were adverse effects and inadequate motor benefit. Most patients who discontinued AI were subsequently treated with another device‐assisted therapy. Conclusion: AI is an effective therapy for severe motor response complications in PD, especially in the short and medium term. However, many patients cannot be maintained on AI in the longer term.